Use of non-face-to-face modalities for emergency department screening, brief intervention, and referral to treatment (ED-SBIRT) for high-risk alcohol use: a scoping review - Biroscak, Brian J. (Subst Abus, 2019)
BACKGROUND: The purpose of this review was to examine and chart the ‘scope’ of strategies reported in ED-SBIRT studies (emergency department-based screening, brief intervention and referral to treatment) that employ non-face-to-face (nFtF) modalities for high-risk alcohol use (i.e., risk for alcohol-related injury, medical condition, use disorder); and to identify research gaps in the scientific literature. METHODS: The scoping review population included study participants with high-risk alcohol use patterns as well as study participants targeted for primary public health prevention (e.g., adolescent ED patients). Core concepts included SBIRT components among intervention studies that incorporated some form of nFtF modality (e.g., computer-assisted brief intervention). The context encompassed ED-based studies or trauma center studies, regardless of geographic location. After screening a total of 1,526 unique references, reviewers independently assessed 58 full-text articles for eligibility. RESULTS: A total of 30 full-text articles were included. Articles covered a period of 14 years (2003–2016) and 19 journal titles. Authors reported the use of a wide range of nFtF modalities across all three ED-SBIRT components: ‘screening’—e.g., computer tablet screening—’brief intervention’—e.g., text-message-based brief interventions—and ‘referral to treatment’—e.g., computer-generated feedback with information about alcohol treatment services. The most frequently used nFtF modality was computerized screening and/or baseline assessment. The main results were mixed with respect to showing evidence of ED-SBIRT intervention effects. CONCLUSIONS: There is an opportunity for substance use disorder researchers to explore the specific needs of several populations—e.g., ED patients with co-occurring problems such as substance use disorder and violence victimization—and on several methodological issues—e.g., ED-SBIRT theory of change. Substance use disorder researchers should take the lead on establishing guidelines for the reporting of ED-SBIRT studies—including categorization schemes for various nFtF modalities. This would facilitate both secondary research (e.g., meta-analyses) and primary research design.